2021
DOI: 10.2217/cer-2020-0201
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of trastuzumab emtansine versus lapatinib plus chemotherapy for HER2+ metastatic breast cancer

Abstract: Aim: To investigate the comparative effectiveness of trastuzumab emtansine (T-DM1) in a real-world population of HER2+ metastatic breast cancer (mBC) patients. Materials and methods: The Flatiron Health database was used to identify a cohort of HER2+ mBC patients who received first-line trastuzumab treatment and T-DM1 or lapatinib plus capecitabine as second-line treatment. Overall survival was compared between the two groups. Results: Three hundred and forty-five patients with HER2+ mBC received second-line T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…On the other hand, the use of T-DM1 became more than twice as frequent as previously observed, highlighting the strategy shift from lapatinib to T-DM1. This is in agreement with the EMILIA trial [ 16 ] results as well as with an RWE study using data from Flatiron Health database that showed a longer OS for patients treated with T-DM1 versus Lapatinib as second-line therapy [ 24 , 25 ]. Nonetheless, trastuzumab alone or in combination with other targeted therapies or chemotherapies remains the preferred choice as third-line in Canada.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, the use of T-DM1 became more than twice as frequent as previously observed, highlighting the strategy shift from lapatinib to T-DM1. This is in agreement with the EMILIA trial [ 16 ] results as well as with an RWE study using data from Flatiron Health database that showed a longer OS for patients treated with T-DM1 versus Lapatinib as second-line therapy [ 24 , 25 ]. Nonetheless, trastuzumab alone or in combination with other targeted therapies or chemotherapies remains the preferred choice as third-line in Canada.…”
Section: Discussionsupporting
confidence: 88%
“… 23 , 25 , 27 , 28 Although the Flatiron/FMI database does not represent a traditional clinical trial comparator, it has previously demonstrated concordance with clinical trial data and has been used as the data source for oncology research across different therapies and indications, including atezolizumab for NSCLC, trastuzumab and lapatinib for human epidermal growth factor receptor 2–positive metastatic breast cancer, and durvalumab and chemotherapy for metastatic urothelial carcinoma. 32 - 34 The dates selected for the Flatiron/FMI patient data (January 2011 to December 2019) were after approval of larotrectinib by the United States and the European Union, but before widespread acceptance of larotrectinib as a SoC for TRK fusion-positive cancers. Exclusion of patients previously treated with TRK inhibitors ensured that the MAIC comparison would restrict the comparison to larotrectinib versus non–TRK-inhibitor SoC.…”
Section: Discussionmentioning
confidence: 99%
“…T-DM1 is a combination of trastuzumab and a chemotherapeutic drug, metanephrine, that retains the activity of trastuzumab monoclonal antibody while delivering potent anti-tumor activity to HER-2 overexpressing tumor cells.According to EMILIA, T-DM1 improved PFS and OS over capecitabine combined with lapatinib in patients with HER-2-positive advanced or MBC treated with trastuzumab and paclitaxel, while Ramagopalan SV et al conducted a real-world study based on the US FH database, and the results further supported T-DM1 therapy as a treatment option for patients with HER-2-positive advanced or MBC [30] . The significant efficacy and good safety of T-DM1 in the treatment of HER-2-positive advanced breast cancer was confirmed by Yan Bingxue et al [31] after performing Meta-analysis.…”
Section: T-dm1mentioning
confidence: 99%